An institution-wide mixed methods assessment of healthcare transition - Anisha Maheshwari; Anna Maria Coronata; Laura Kirkpatrick; Ahmed Abdul-Al; Andrew McCormick; Loreta Matheo; Traci M. Kazmerski (Health Care Transitions)
Background: Healthcare transition (HCT) is the process of moving a patient from pediatric, parent-supervised care to an independent, adult-centered model. This study assesses current HCT activities and explores the educational and system-based needs for effective HCT processes in a single institution. Methods: We interviewed division/care program leaders at one academic tertiary-care children’s hospital regarding HCT practices. We evaluated these groups using an interview guide and rubric scoring from the “GotTransition Current Assessment of HCT Activities” (scoring range from 8 [low HCT] to 32 [high HCT]). We audio-recorded and transcribed interviews. We calculated each group’s score on the rubric. Two coders qualitatively analyzed interview transcripts using a thematic analysis approach with deductive and inductive strategies. Results: We interviewed 28 participants, each representing one division/care program. The institutional mean on the HCT assessment was 15.5 ± 4.5 (median 17.5, range 8–28). Key interview themes included: 1) Significant heterogeneity in the HCT process exists within most divisions/care programs; 2) While some groups have their own HCT practices, there is no coordinated institutional HCT approach.; 3) Participants find HCT difficult if they perceive the lack of an equivalent adult specialist for a patient’s specific medical condition; 4) There is a lack of coordinated handoffs from pediatric to adult providers. 5) Participants desire ancillary staff to support HCT. Conclusion: Despite known benefits of a structured approach, most leaders report heterogeneity in current HCT practices and a lack of institutional resources and adult provider partners to support optimal HCT. We present a reproducible methodology to evaluate HCT within a single institution, as well as baseline assessment data that may inform interventions.